2011
DOI: 10.1097/nan.0b013e31820b7899
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Dilution on Intravenous Therapy

Abstract: Chemically induced phlebitis continues to be an adverse reaction from the intravenous administration of infusates. The primary method used for decreasing the incidence of chemically induced phlebitis is to dilute infusates to the point where they do not cause tissue damage. The exact amount of dilution required for preventing chemically induced phlebitis is not currently known. This article describes methods for accurately determining the onset of chemically induced phlebitis and for describing the final conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 21 publications
(21 reference statements)
0
6
0
5
Order By: Relevance
“…However, Everitt made no reference to the presence or absence of subcutaneous edema. In contrast, LaRue and Peterson suggested that the toxicant is no more diluted when a catheter's tip is positioned perpendicularly to the vessel wall; therefore, it may promote the incidence of chemically-induced phlebitis and subcutaneous edema (18). However, they did not observe the position of the catheter within the vein.…”
Section: Discussionmentioning
confidence: 67%
“…However, Everitt made no reference to the presence or absence of subcutaneous edema. In contrast, LaRue and Peterson suggested that the toxicant is no more diluted when a catheter's tip is positioned perpendicularly to the vessel wall; therefore, it may promote the incidence of chemically-induced phlebitis and subcutaneous edema (18). However, they did not observe the position of the catheter within the vein.…”
Section: Discussionmentioning
confidence: 67%
“…20 After multiple venipuncture attempts, a clot can form inside the vein lumen. A larger catheter relative to the vein decreases blood flow, 21 which would promote thrombus growth. Thrombus may lead to complete occlusion of the vein.…”
Section: Discussionmentioning
confidence: 99%
“…Por isso, o efeito da diluição é maior quando a ponta do lúmen do cateter está localizada no centro exato do lúmen do vaso. 25 Para que as práticas de segurança na TIV sejam discutidas e implementadas, é necessário que os dirigentes das organizações estejam engajados no desenvolvimento da cultura de segurança voltada para o paciente e organizem uma equipe multidisciplinar que lidere essas discussões, buscando analisar e avaliar cada processo existente, em busca de melhorias.…”
Section: Discussionunclassified